Directions of changes in reporting of units of territorial self-government - Wakuła, Monika (Management and Administration Journal, 2023)
Reporting includes a systematised collection of information created by accounting and outside accounting. The information should be useful in taking managing decisions and evaluating the financial situation of a unit of territorial self-government. The present system of reporting in the selfgoverning sector does not provide such data. Therefore, changes are needed that would aim at implementing such forms of reporting that will fulfill the statistical and informative goals of the state budget and will satisfy the informative needs of units of the territorial self-government within the scope of managing and evaluating the conducted financial economy.